Lignin-based carrier iron-carbon material, preparation method and application thereof
Patent Information
- Application Number
- CN202611314262.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-27
- Publication Date
- 2026-10-16
AI Technical Summary
但这些方法普遍存在吸附量小、吸附效率低、易产生有害副产物等局限,因而开发具有高效吸附率、低成本、高比表面积、易于分离回收、对废水中污染物吸附能力强的生物碳材料具有重要的经济效益和环境效益
本发明利用木质素基载铁碳骨架的丰富孔隙结构提供传质通道和吸附位点,同时通过FeOOH晶体表面的羟基基团与酚类分子形成强烈的氢键作用,并提升碳材料的亲水性以增强水渗透性和传质效率,多孔碳骨架与FeOOH晶体之间产生协同增效作用,显著优于不含FeOOH的多孔碳材料。
Smart Images

Figure CN122912805A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wastewater treatment technology, specifically to lignin-based iron-carrying carbon materials, their preparation methods, and applications. Background Technology
[0002] Water resources are a fundamental guarantee for human survival; however, water scarcity, uneven distribution, and pollution have seriously threatened the human living environment. Phenolic wastewater is one of the most significant organic wastewaters in industry, characterized by its complex composition, high toxicity, and high treatment costs and difficulties. Currently, phenolic pollutants are listed as priority pollutants by the U.S. Environmental Protection Agency and the European Union, and the treatment of phenolic organic wastewater has received widespread attention.
[0003] Currently, commonly used physicochemical methods for treating phenol-containing wastewater include activated carbon adsorption, ion exchange resin adsorption, photocatalytic degradation, and hydrogen peroxide oxidation. However, these methods generally have limitations such as low adsorption capacity, low adsorption efficiency, and easy generation of harmful byproducts. Therefore, developing biochar materials with high adsorption rate, low cost, high specific surface area, easy separation and recovery, and strong adsorption capacity for pollutants in wastewater has significant economic and environmental benefits.
[0004] In view of this, the present invention is proposed. Summary of the Invention
[0005] The present invention aims to solve at least any of the above technical problems, and provides lignin-based iron-carrying carbon materials, their preparation methods and applications.
[0006] To achieve the above objectives, the first technical solution adopted by the present invention is as follows: The lignin-based iron-carbon material has a lignin-based porous carbon skeleton and FeOOH crystals loaded on the surface of the skeleton. The porous carbon skeleton has a loose porous network structure, and the surface of the FeOOH crystals is rich in hydroxyl groups.
[0007] Preferably, the lignin-based iron-supported carbon material is prepared by high-temperature carbonization, washing, and hydrothermal activation at 120~160 °C of lignin compounds, boric acid, and ferric chloride.
[0008] Preferably, the lignin compound is alkali lignin or sodium lignin sulfonate.
[0009] Preferably, by weight, the lignin compound comprises 2-4 parts, boric acid comprises 8-20 parts, and ferric chloride comprises 5-10 parts.
[0010] The second technical solution adopted in this invention is: Methods for preparing lignin-based iron-supported carbon materials include: Lignin compounds, boric acid, and ferric chloride are mixed and reacted in deionized water. After drying, the mixture is carbonized at high temperature under an inert atmosphere. The carbonized material is then washed and hydrothermally activated in deionized water at 120-160 °C for 4-12 hours.
[0011] Preferably, by mass, the deionized water comprises 150-200 parts, the lignin compounds comprise 2-4 parts, the boric acid comprises 8-20 parts, and the ferric chloride comprises 5-10 parts.
[0012] Preferably, the lignin compound is alkali lignin or sodium lignin sulfonate.
[0013] Preferably, the mixing reaction is carried out at 60~80 °C for 4~8 h; the high-temperature carbonization is carried out under nitrogen protection by heating to 800~900 °C at 5 °C / min for 2 h; the washing includes acid washing and water washing.
[0014] The third technical solution adopted in this invention is: Application of lignin-based iron-carbon materials in the treatment of phenol-containing wastewater.
[0015] Preferably, the method of application is to add lignin-based iron-supported carbon material to phenol-containing wastewater, and then separate it after stirring and adsorption at room temperature; The dosage of lignin-based iron-supported carbon material is 30-80 mg per 25 mL of phenol-containing wastewater. The stirring and adsorption time is 5 min to 24 h.
[0016] Compared with the prior art, the present invention has the following beneficial effects: This invention utilizes the abundant porous structure of the lignin-based iron-supported carbon skeleton to provide mass transfer channels and adsorption sites. At the same time, the hydroxyl groups on the surface of FeOOH crystals form strong hydrogen bonds with phenolic molecules, thereby enhancing the hydrophilicity of the carbon material to improve water permeability and mass transfer efficiency. The porous carbon skeleton and FeOOH crystals produce a synergistic effect, which is significantly better than porous carbon materials without FeOOH.
[0017] The lignin-based iron-supported carbon material prepared by this invention can maintain high adsorption activity in a wide pH range of 4 to 9, and the removal rate of phenolic pollutants such as phenol can reach more than 92%, and up to 100%, with a fast adsorption rate.
[0018] The lignin-based iron-supported carbon material of the present invention has good structural stability. After six adsorption-desorption cycles, the removal rate of phenol is still greater than 90%. At the same time, the iron loss is small, which effectively avoids the problem of secondary pollution during the treatment process. Attached Figure Description
[0019] Figure 1HRTEM characterization image of the lignin-based iron-carbon supported material prepared in Example 1 (FeOOH(530) crystal plane); Figure 2 TEM image of the lignin-based iron-supported carbon material prepared in Example 1; Figure 3 SEM image of the lignin-based iron-supported carbon material prepared in Example 2; Figure 4 The image shows a TEM image of the adsorbent prepared in Comparative Example 3. Detailed Implementation
[0020] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] The first embodiment of the present invention provides a lignin-based iron-carbon material having a lignin-based porous carbon skeleton and FeOOH crystals loaded on the surface of the skeleton. The porous carbon skeleton has a loose porous network structure, and the surface of the FeOOH crystals is rich in hydroxyl groups.
[0022] The lignin-based iron-supported carbon material provided by this invention uses a lignin-based porous carbon material as its framework. This lignin-based porous carbon framework has a loose and well-developed porous network structure, which facilitates abundant mass transfer channels and adsorption sites. FeOOH crystals are loaded onto the surface of the porous carbon framework and distributed on the pore walls of the porous network structure. The FeOOH crystal surface is rich in hydroxyl groups (-OH), which can form strong hydrogen bonds with phenol molecules, endowing the material with directional chemical recognition capabilities for phenolic pollutants, thereby improving adsorption efficiency. Furthermore, the carbon material surface is relatively hydrophobic, which is unfavorable for the access of phenol in the aqueous phase. The introduction of FeOOH can significantly improve the hydrophilicity of the carbon material, thereby enhancing water permeability and the mass transfer efficiency of phenol molecules to the active sites.
[0023] This lignin-based iron-supported carbon material is prepared by high-temperature carbonization, washing, and hydrothermal activation at 120-160°C of lignin compounds, boric acid, and ferric chloride. The lignin compounds are those capable of providing a carbonaceous skeleton, including but not limited to alkali lignin, sodium lignin sulfonate, sulfate lignin, organic solvent lignin, or enzymatically hydrolyzed lignin; preferably alkali lignin or sodium lignin sulfonate. By weight, the lignin compounds may be 2-4 parts, the boric acid may be 8-20 parts, and the ferric chloride may be 5-10 parts.
[0024] The preparation method of the lignin-based iron-supported carbon material includes the following steps: mixing and reacting lignin compounds, boric acid and ferric chloride in deionized water, drying and then carbonizing at high temperature under an inert atmosphere, and after washing, hydrothermally activating the carbonized material in deionized water at 120~160℃ for 4~12h.
[0025] The second embodiment of the present invention provides a method for preparing lignin-based iron-supported carbon materials, comprising: Lignin compounds, boric acid, and ferric chloride are mixed and reacted in deionized water. After drying, the mixture is carbonized at high temperature under an inert atmosphere. The carbonized material is then washed and hydrothermally activated in deionized water at 120-160°C for 4-12 hours.
[0026] The mixing reaction can be carried out at 60-80℃ for 4-8 hours. The mixing reaction can be conducted in a conventional reaction vessel, using mechanical stirring to achieve homogeneity; this is a standard operating procedure in chemical synthesis. After the reaction is complete, moisture is removed by evaporation and drying to obtain a dried precursor. Evaporation and drying can employ commonly used methods in this field, such as oven drying or vacuum drying, as long as the moisture is removed to a degree suitable for subsequent carbonization.
[0027] By mass, deionized water can be 150-200 parts, lignin compounds can be 2-4 parts, boric acid can be 8-20 parts, and ferric chloride can be 5-10 parts. Among these raw materials, lignin compounds serve as a carbon source, boric acid acts as an activator / template during subsequent high-temperature carbonization to promote the formation of a porous network structure, and ferric chloride serves as an iron source, providing a precursor for the subsequent formation of FeOOH crystals. The three are used synergistically, achieving a uniform composite of carbon source, pore-forming agent, and iron source through a one-step blending process.
[0028] The dried precursor is carbonized at high temperature under an inert atmosphere. The inert atmosphere can be nitrogen, argon, or other commonly used inert protective gases in the art to prevent oxidation of the carbon material at high temperatures. High-temperature carbonization can be carried out under nitrogen protection, with the temperature increased at 5 °C / min to 800-900 °C for 2 hours. The carbonization temperature and time can be adjusted according to conventional techniques in the art, as long as the lignin compounds are fully converted into a carbonaceous framework while simultaneously allowing boric acid to play a pore-forming role. During carbonization, B₂O₃ and other substances produced by the decomposition of boric acid can act as template agents to enrich the pore structure, while iron species are initially embedded in the carbon framework.
[0029] The carbonized material is washed, including acid washing and water washing. First, hydrochloric acid is used for acid washing to remove unstable iron oxides. During carbonization, some iron species exist in the form of free or weakly bound unstable iron oxides. These unstable iron oxides are easily lost during subsequent applications, causing not only the loss of active sites but also potential secondary pollution. Hydrochloric acid washing selectively removes these unstable iron oxides, retaining iron species that are relatively firmly bound to the carbon framework, laying the foundation for the subsequent hydrothermal activation and directional formation of stable FeOOH crystals.
[0030] After pickling, the product is washed with water to remove boron oxide and residual hydrochloric acid. The water wash can be performed sequentially using deionized water and ethanol. First, deionized water is used to remove residual hydrochloric acid and soluble salts, followed by ethanol washing to remove residual boron oxide and other substances, which also facilitates subsequent drying. Water washing is a standard procedure in this field, and the number of washes and the amount of solvent used can be determined by those skilled in the art based on the actual washing effect.
[0031] Hydrothermal activation is carried out under mild hydrothermal conditions of 120–160 °C. The iron species retained after acid washing undergo a hydrothermal reaction in deionized water, directionally transforming into FeOOH crystals with stable crystal structure and rich hydroxyl content on the surface. This hydrothermal activation can be performed in a reactor, a conventional device in the field of hydrothermal synthesis. The hydrothermal activation temperature and time can be adjusted within the above range according to technical means in this field, as long as the residual iron species are fully converted into FeOOH crystals. This mild hydrothermal activation achieves directional control of the crystal structure of the iron active sites, allowing FeOOH crystals to be firmly loaded onto the surface of the lignin-based porous carbon framework, thereby ensuring the material's adsorption activity and low iron loss characteristics over a wide pH range. If only a one-step high-temperature carbonization method is used without this hydrothermal activation step, although the iron species in the carbon framework may partially transform into iron oxides, they usually exist in a mixed form of multiple phases and are prone to severe agglomeration due to high-temperature sintering, making it difficult to form FeOOH crystals with a single crystal structure and uniform dispersion.
[0032] The third embodiment of the present invention provides the application of lignin-based iron-carbon materials in the treatment of phenol-containing wastewater.
[0033] The method involves adding lignin-based iron-supported carbon material as an adsorbent to phenol-containing wastewater, and then separating the adsorbent by stirring at room temperature.
[0034] The amount of lignin-based iron-supported carbon material used can be 30-80 mg per 25 mL of phenol-containing wastewater. The stirring adsorption time can be 5 min to 24 h. After stirring adsorption, the adsorbent can be removed by conventional solid-liquid separation methods in the art, such as filtration and centrifugation, and the phenol concentration in the solution can be tested to calculate the removal rate.
[0035] The phenol-containing wastewater can be wastewater containing phenolic compounds such as phenol, hydroquinone, p-cresol, or 4-methoxyphenol. The concentration of the phenol-containing solution can be around 50 mg / L. In practical applications, the amount of adsorbent and the adsorption time can be adjusted according to the wastewater concentration.
[0036] The adsorption of phenol-containing wastewater by the material of this invention is the result of a synergistic effect of physical adsorption and chemical action. Porous carbon materials, with their large specific surface area, are advantageous for adsorbing phenolic pollutants in wastewater. The π-π stacking interactions, hydrogen bonding, and electrostatic interactions between the carbon material and phenolic pollutants also enhance the material's adsorption capacity for phenol-containing wastewater. The FeOOH crystal surface possesses numerous hydroxyl groups (-OH), which can form strong hydrogen bonds with phenol molecules. This chemical affinity gives FeOOH a directional chemical recognition ability for phenol adsorption, thereby improving adsorption efficiency. Simultaneously, the introduction of FeOOH significantly enhances the hydrophilicity of the carbon material, improving water permeability and the mass transfer efficiency of phenol molecules to the active sites.
[0037] The preparation and properties of lignin-based iron-carrying carbon materials are described in detail below through several examples.
[0038] In the following application of lignin-based iron-carbon materials, a phenol-containing solution was used to simulate phenol-containing wastewater. This phenol-containing solution was prepared by dissolving phenol in deionized water, and the concentration was determined according to experimental needs (e.g., 50 mg / L or 60 mg / L). The pH of the phenol-containing solution was adjusted to 4-9 to simulate phenol-containing wastewater under different acidic and alkaline conditions.
[0039] A quantitative amount of lignin-based iron-supported carbon material was added to the above phenol-containing solution and placed in a shaker for adsorption at room temperature. After adsorption, the lignin-based iron-supported carbon material was removed by centrifugation, and the supernatant was collected. The fluorescence intensity of the residual phenolic substances in the solution was determined by fluorescence spectrophotometry, and the concentration C of the residual phenolic substances in the solution after treatment (at time t) was calculated based on a pre-plotted standard curve. t And the concentration C0 of phenolic substances in the initial solution before treatment.
[0040] The phenol removal rate is calculated based on the change in phenol concentration in the solution before and after treatment, and the calculation formula is as follows: Phenol removal rate (%) = (C0 - C) t ) / C0× 100%.
[0041] Example 1: Preparation of lignin-based iron-supported carbon materials 150 g of deionized water, 2 g of alkali lignin, and 10 g of boric acid were mixed evenly, and 6 g of ferric chloride was added. The mixture was stirred at 80 °C for 6 h, and then evaporated and dried to obtain the dried precursor. The precursor was then carbonized at 800 °C for 2 h under N2 protection with a heating rate of 5 °C / min. The carbonized material was first acid-washed with 1M hydrochloric acid to remove unstable iron oxides, and then washed with deionized water and ethanol to remove boron oxide and residual hydrochloric acid, resulting in a porous iron-supported carbon material. Deionized water was added to the porous iron-supported carbon material, and it was activated at 140 °C for 6 h to obtain a lignin-based iron-supported carbon material.
[0042] Figure 1 HRTEM (High Resolution Transmission Electron Microscopy) characterization image of the lignin-based iron-carrying carbon material prepared for this embodiment; Figure 1 Intensity distribution analysis of the lattice fringes showed an interplanar spacing of 1.82 nm, which is consistent with the theoretical d-value of the FeOOH (530) crystal plane in the same standard card. Different crystal plane indices confirm that the iron oxide loaded on the surface of the material of this invention exists in the form of crystalline FeOOH.
[0043] Figure 2 TEM images of the lignin-based iron-supported carbon material prepared for this embodiment are provided by Figure 2 It can be seen that after hydrothermal activation at 120~160℃, the metal particles are refined and uniformly dispersed on the surface of the carbon framework, with no obvious agglomeration. TEM images of the material prepared in Comparative Example 3 are shown below. Figure 4 The comparison shows that the hydrothermal activation step not only achieves the directional transformation of iron species into FeOOH crystal form, but also significantly improves the dispersion of metal particles on the carbon skeleton, which is beneficial to improving the exposure of active sites and adsorption performance.
[0044] Example 2 Preparation of lignin-based iron-supported carbon materials 200 g of deionized water, 4 g of sodium lignosulfonate, and 18 g of boric acid were mixed evenly, and 10 g of ferric chloride was added. The mixture was stirred at 70 °C for 8 h, and then evaporated and dried to obtain the dried precursor. The precursor was then carbonized at 800 °C for 2 h under N2 protection with a heating rate of 5 °C / min. The carbonized material was first washed with 1M hydrochloric acid to remove unstable iron oxides, and then washed with deionized water and ethanol to remove boron oxide and residual hydrochloric acid, resulting in a porous iron-supported carbon material. Deionized water was added to the porous iron-supported carbon material, and it was activated at 120 °C for 8 h to obtain a lignin-based iron-supported carbon material.
[0045] Figure 3 SEM images of the lignin-based iron-supported carbon material prepared for this embodiment, from... Figure 3It can be seen that the material exhibits a highly loose and well-developed porous network structure with well-developed pores and cross-linked pore walls, which is conducive to providing abundant three-dimensional mass transfer channels and adsorption sites, and ensuring the effective loading and exposure of FeOOH crystals on the pore wall surface, thereby significantly promoting its adsorption and capture capacity for phenolic pollutants.
[0046] Example 3: Application of lignin-based iron-carrying carbon materials Take 25 mL of phenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 50 mg of the lignin-based iron-supported carbon material prepared in Example 1, and then place it in a shaker and shake for 24 h. The phenol removal rate is 99.5%.
[0047] Example 4: Application of lignin-based iron-carrying carbon materials Take 25 mL of hydroquinone solution (60 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 50 mg of the lignin-based iron-carbon material prepared in Example 1, and then place it in a shaker and shake for 24 h. The hydroquinone removal rate is 98.6%.
[0048] Example 5: Application of lignin-based iron-carrying carbon materials Take 25 mL of p-cresol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 6, add 50 mg of the lignin-based iron-carrying carbon material prepared in Example 1, and then place it in a shaker and shake for 24 h. The p-cresol removal rate is 98.8%.
[0049] Example 6: Application of lignin-based iron-carrying carbon materials Take 25 mL of phenol solution (60 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 9, add 60 mg of the lignin-based iron-carbon material prepared in Example 1, and then place it in a shaker and shake for 8 h. The phenol removal rate is 96.7%.
[0050] Example 7: Application of lignin-based iron-carrying carbon materials Take 25 mL of phenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 8, add 40 mg of the lignin-based iron-carrying carbon material prepared in Example 1, and then place it in a shaker and shake for 5 min. The phenol removal rate is 92.1%.
[0051] The results show that the lignin-based iron-supported carbon material of this invention can achieve a high phenol removal rate in a very short time (5 min), demonstrating excellent adsorption kinetics performance. With the extension of adsorption time, the material can further achieve an even higher equilibrium removal rate.
[0052] Example 8: Application of lignin-based iron-carrying carbon materials Take 25 mL of phenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 6, add 50 mg of the lignin-based iron-carbon material prepared in Example 2, and then place it in a shaker and shake for 12 h. The phenol removal rate is 99.4%.
[0053] Example 9: Application of lignin-based iron-carrying carbon materials Take 25 mL of phenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 50 mg of the lignin-based iron-carbon material prepared in Example 2, and then place it in a shaker and shake for 24 h. The phenol removal rate is 100%.
[0054] Example 10 Application of lignin-based iron-carbon materials Take 25 mL of 4-methoxyphenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 45 mg of the lignin-based iron-carbon material prepared in Example 2, and then place it in a shaker and shake for 5 min. The removal rate of 4-methoxyphenol is 99.1%.
[0055] Example 11 Application of lignin-based iron-carrying carbon materials Take 25 mL of 2,4-dichlorophenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 50 mg of the lignin-based iron-carbon material prepared in Example 2, and then place it in a shaker and shake for 12 h. The removal rate of 2,4-dichlorophenol is 100%.
[0056] Comparative Example 1 Iron-free porous carbon materials were prepared. Compared with Example 2, only ferric chloride was not added to the precursor solution; all other raw materials and preparation processes were the same as in Example 2.
[0057] The FeOOH-free porous carbon material obtained from this comparative example was used to conduct a phenol adsorption test. 25 mL of phenol solution (50 mg / L) was placed in an Erlenmeyer flask, the pH was adjusted to 7, and 50 mg of the FeOOH-free porous carbon material was added. The flask was then placed in a shaker and shaken for 24 h. After treatment using this process, the phenol removal rate was 90.8%.
[0058] The results show that the porous carbon material without FeOOH achieved a phenol removal rate of 90.8% after 24 hours of shaking. In contrast, using the same preparation process with only ferric chloride added, the resulting lignin-based iron-supported carbon material achieved a removal rate of over 92% within 5 minutes, and this rate reached over 99% after 24 hours of adsorption. This comparison demonstrates that the introduction of FeOOH not only significantly improved the equilibrium adsorption capacity of the material but also greatly shortened the time required to achieve a high removal rate, exhibiting excellent adsorption kinetics for phenolic pollutants.
[0059] Comparative Example 2 The adsorbent for this comparative example was prepared according to the method in Example 1, except that the addition of boric acid was omitted.
[0060] Take 25 mL of phenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 50 mg of the adsorbent prepared in this comparative example, and then place it in a shaker and shake for 24 h. The removal rate is 91.2%.
[0061] Comparative Example 3 The adsorbent for this comparative example was prepared according to the method in Example 1, except that the final activation step was omitted. The specific method was as follows: 150 g of deionized water, 2 g of alkali lignin and 10 g of boric acid were mixed evenly, 6 g of ferric chloride was added, and the mixture was stirred at 80 °C for 6 h. The mixture was then evaporated and dried to obtain the dried precursor. Subsequently, the precursor was carbonized at 800 °C for 2 h under N2 protection by heating at 5 °C / min. The carbonized material was first washed with 1 M hydrochloric acid to remove unstable iron oxides, and then washed with deionized water and ethanol to remove boron oxide and residual hydrochloric acid.
[0062] Take 25 mL of phenol solution (50 mg / L) into a 250 mL Erlenmeyer flask, adjust the pH to 7, add 50 mg of the adsorbent prepared in this comparative example, and then place it in a shaker and shake for 24 h. The removal rate is 90.7%.
[0063] Figure 4 The TEM image of the adsorbent prepared in this comparative example shows that the metal particles in the adsorbent that has not been hydrothermally activated are distributed in large agglomerates and are unevenly dispersed.
[0064] Cyclic stability test: For adsorption stability evaluation, 50 mg of the lignin-based iron-supported carbon material prepared in Example 2 was used to adsorb 25 mL of a phenol solution with a concentration of 50 mg / L for 24 h. The pH of the repeated experiment was 7. After adsorption, the adsorbent was separated by centrifugation, washed with deionized water to remove residual phenol, and then desorbed by sonication with ethanol for 4 h. After desorption, the adsorbent was separated by centrifugation, washed with deionized water to remove residual ethanol, and dried at 60-80 °C to constant weight. The regenerated adsorbent was then added to a fresh phenol solution, and the above adsorption-separation-desorption-drying steps were repeated for a total of 6 cycles. The experimental results are shown in Table 1 below.
[0065] Table 1 .
[0066] As shown in Table 1, the lignin-based iron-supported carbon material maintained a removal rate of over 90% after six adsorption-desorption cycles, which is higher than most reported phenol adsorbents. This indicates that the FeOOH-supported porous carbon material of this invention possesses good structural stability and has potential for reuse.
[0067] The embodiments described above are some, but not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art through related deductions and substitutions based on the inventive concept, without inventive effort, are within the scope of protection of the present invention.
Claims
1. A lignin-based iron-carbon supported material, characterized in that, It has a lignin-based porous carbon skeleton and FeOOH crystals supported on the surface of the skeleton. The porous carbon skeleton has a loose porous network structure, and the surface of the FeOOH crystals is rich in hydroxyl groups.
2. The lignin-based iron-supported carbon material as described in claim 1, characterized in that, The lignin-based iron-supported carbon material is prepared by high-temperature carbonization, washing, and hydrothermal activation at 120-160°C of lignin compounds, boric acid, and ferric chloride.
3. The lignin-based iron-supported carbon material as described in claim 2, characterized in that, The lignin compound is alkali lignin or sodium lignin sulfonate.
4. The lignin-based iron-supported carbon material as described in claim 2, characterized in that, By mass, lignin compounds comprise 2-4 parts, boric acid comprises 8-20 parts, and ferric chloride comprises 5-10 parts.
5. A method for preparing lignin-based iron-supported carbon materials, characterized in that, include: Lignin compounds, boric acid, and ferric chloride are mixed and reacted in deionized water. After drying, the mixture is carbonized at high temperature under an inert atmosphere. The carbonized material is then washed and hydrothermally activated in deionized water at 120-160°C for 4-12 hours.
6. The preparation method according to claim 5, characterized in that, By mass, the components are: 150-200 parts deionized water, 2-4 parts lignin compounds, 8-20 parts boric acid, and 5-10 parts ferric chloride.
7. The preparation method according to claim 5, characterized in that, The lignin compound is alkali lignin or sodium lignin sulfonate.
8. The preparation method according to claim 5, characterized in that, The mixing reaction is carried out at 60~80 °C for 4~8 h; the high-temperature carbonization is carried out under nitrogen protection by heating to 800~900 °C at 5 °C / min for 2 h; the washing includes acid washing and water washing.
9. The application of the lignin-based iron-supported carbon material as described in any one of claims 1-4, or the lignin-based iron-supported carbon material obtained by the preparation method as described in any one of claims 5-8, in the treatment of phenol-containing wastewater.
10. The application as described in claim 9, characterized in that, The method involves adding lignin-based iron-supported carbon material to phenol-containing wastewater, stirring and adsorbing it at room temperature, and then separating the adsorbed material. The dosage of lignin-based iron-supported carbon material is 30-80 mg per 25 mL of phenol-containing wastewater. The stirring and adsorption time is 5 min to 24 h.